2021
DOI: 10.1017/s000712342100034x
|View full text |Cite
|
Sign up to set email alerts
|

Casting Ballots When Knowing Results

Abstract: Access to information about candidates' performance has long stood as a key factor shaping voter behaviour, but establishing how it impacts behaviour in real-world settings has remained challenging. In the 2018 Brazilian presidential elections, unpredictable technical glitches caused by the implementation of biometrics as a form of identification led some voters to cast ballots after official tallies started being announced. In addition to providing a source of exogenous variation of information exposure, run-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Particularly strong evidence in favor of the bandwagon effect comes for example from a recent analysis of voting data collected during the 2018 Brazilian presidential elections, in which technical glitches caused some voters to cast their ballots after initial results were announced. Results suggested a sizeable bandwagon and no underdog effect (Araújo & Gatto, 2022). Other strong evidence for a bandwagon effect comes from a controlled experiment, which showed that participants were more likely to donate to charities that received the support of a majority of other participants (Farjam, 2021).…”
Section: Bandwagon Vs Underdog Effectsmentioning
confidence: 98%
“…Particularly strong evidence in favor of the bandwagon effect comes for example from a recent analysis of voting data collected during the 2018 Brazilian presidential elections, in which technical glitches caused some voters to cast their ballots after initial results were announced. Results suggested a sizeable bandwagon and no underdog effect (Araújo & Gatto, 2022). Other strong evidence for a bandwagon effect comes from a controlled experiment, which showed that participants were more likely to donate to charities that received the support of a majority of other participants (Farjam, 2021).…”
Section: Bandwagon Vs Underdog Effectsmentioning
confidence: 98%